Small Molecule Probes for Plant Cell Wall Polysaccharide Imaging - Wallace, Ian; Anderson, Charles T. (Frontiers in Plant Science, 2012)
Plant cell walls are composed of interlinked polymer networks consisting of cellulose, hemicelluloses, pectins, proteins, and lignin. The ordered deposition of these components is a dynamic process that critically affects the development and differentiation of plant cells. However, our understanding of cell wall synthesis and remodeling, as well as the diverse cell wall architectures that result from these processes, has been limited by a lack of suitable chemical probes that are compatible with live-cell imaging. In this review, we summarize the currently available molecular toolbox of probes for cell wall polysaccharide imaging in plants, with particular emphasis on recent advances in small molecule-based fluorescent probes. We also discuss the potential for further development of small molecule probes for the analysis of cell wall architecture and dynamics.